2020
DOI: 10.12659/msm.920252
|View full text |Cite
|
Sign up to set email alerts
|

Active Surveillance of Prostate Cancer Using Multiparametric Magnetic Resonance Imaging: A Review of the Current Role and Future Perspectives

Abstract: Departmental sourcesClinically, active surveillance involves continuous monitoring of patients who may be at risk for disease. Patients with low-grade and early-stage prostate cancer may benefit from active surveillance, rather than undergoing surgical and medical treatments that are associated with side effects. In these cases, the role of active surveillance is to ensure that there is no progression of the disease. However, active surveillance may be associated with a risk of under-diagnosis. Previously, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 55 publications
1
14
0
1
Order By: Relevance
“…A previously published study reported that RO3280 exerts antitumor effects, facilitated predominantly by DNA damage, cell cycle arrest, and apoptosis in breast cancer cells [2]. In our previous study too, we found that RO3280 repressed bladder carcinoma growth through G2/M arrest and mitotic arrest [6].…”
Section: P R E P R I N Tsupporting
confidence: 56%
See 1 more Smart Citation
“…A previously published study reported that RO3280 exerts antitumor effects, facilitated predominantly by DNA damage, cell cycle arrest, and apoptosis in breast cancer cells [2]. In our previous study too, we found that RO3280 repressed bladder carcinoma growth through G2/M arrest and mitotic arrest [6].…”
Section: P R E P R I N Tsupporting
confidence: 56%
“…Prostate cancer is among the most pernicious tumors of the genitourinary system and is the second most commonly observed cause of cancer-related death among men in Western countries [1]. The diverse clinical behaviors of prostate cancer include a sloth-like characteristic with little or no clinical value, invasive metastasis, and lethality [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Selvi et al reported that arginine and its metabolites, including plasma arginine, ornithine, arginine to ornithine ratio, and urinary diacetylspermine, could be used as molecular markers to predict PCa when the PSA level is in the gray area, and these biomarkers could be an important research focus in diagnosing PCa [ 40 ]. Third, active surveillance (AS), a strategy of management of patients with low-risk prostate cancer, could reduce unnecessary over-treatment [ 41 ]. A meta-analysis found the mpMRI-targeted biopsy is a useful addition to systematic confirmation in patients on AS with low-risk PCa [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, most (82.6%) of the MRI-invisible lesions from the study were low risk based on Decipher testing, suggesting the addition of Decipher to MRI may not yield significantly more detection of CS cancer. 48 …”
Section: Tests For Men On Active Surveillancementioning
confidence: 99%